Vegyes választott döntőbíróságok : Fiume területén keletkezett pénzügyi kérdések rendezése - Szávai, Ferenc (Közép-Európai Közlemények, 2013)
The work of mixed court of arbitration (the closing of financial issues of the late Fiume). The closing peace-treaties of the First World War caused several conflicts between the majority and minorities in a particular national country. We can find several petition, prayer and requests on financial, social and nationality issues from this period. The League of Nations ensured the peace in the international field and delegated the conflict’s disposal to the arbitration court to be able to solve the problem of the controversial territories in a peaceful way. One of these organization was the Hungarian-Italian arbitration court (with particular attention devoted to the issues of Fiume) where Hungary has been represented – next to his several arbitrational work – by Joseph Szterényi.